This equals [f(3) - f(1)] / [3-1]
= 3^2 + 6(3) + 10 - (1^2 + 6(1) + 10) / 2
= (37 - 17) / 2
= 10 Answer
Answer:
When the input is 6, the output must be 12.
Step-by-step explanation:
f(6) = 12
The input to the function is x which is 6 and the output is what f(6) equals which is 12
Step-by-step explanation:
100 multiple it by the percentage
We have been given that Anil borrows $80 000 to buy a business. The bank gives him a loan, with an interest rate of 2% each year. We are asked to find the total amount paid back by Anil to bank after 10 years.
We will use simple interest formula to solve our given problem.
, where,
A = Final amount,
P = Principal amount,
r = Annual interest rate in decimal form,
t = Time in years.
Let us convert 2% into decimal.

We have
and
, so we will get:




Therefore, Anil will pay
to the bank after 10 years.
Answer:
Yeah I would be too
Step-by-step explanation: